(untitled) (Global Journal of Human-Social Science, 2021)
The Illustração Paranaense: mensario paranista de arte e actualidades was a magazine that circulated in Paraná, Brazil between 1927 and 1930, during which the Paranista Movement lived its heyday. Counting practices of different fields, this cultural movement developed to mobilize awareness and actions of artists and intellectuals in favor of a local identity. The intention is to take as object of study the role of that magazine in the construction of both a speech, as images, they intended to set a paranaense identity. The aim of this article is to understand how the periodic exercised its role as a vehicle for the dissemination of ideas and works of representatives of Paranista Movement, the specificity of the visual arts. Is taken as hypothesis that political interest is not excelled on the artistic and cultural interest, because both followed the same direction. Drawing on statistical data, the intention is investigate the relationship network formed by the editorial staff of the magazine and its contributors.